1997
DOI: 10.1111/j.1432-1033.1997.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Wound‐Induced Myrosinase‐Associated Protein Transcript in Brassica Napus Plants

Abstract: Two slightly differing cDNA clones corresponding to the wound-inducible form of a previously characterized seed myrosinase-associated protein (MyAP) have been isolated from Brassica nupus L. The transcripts corresponding to the induced MyAP (iMyAP) were found to be developmentally regulated in various vegetative organs. Both young and old leaves exhibited wound-inducible iMyAP expression. Furthermore, in the young plant, wounding resulted in a systemic increase in leaves located both acropetally and basipetall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 55 publications
1
39
1
Order By: Relevance
“…However, two myrosinase-like genes (BGL1, At1g52400 and At5g28510) were strongly up-regulated during K 1 starvation (average fold change of 8.6 and 7.6, respectively) and down-regulated upon K 1 resupply. Furthermore, several myrosinase-binding protein, homologs of which are induced by wounding and exogenous JA treatment in Brassica napus (Taipalensuu et al, 1997), showed the same expression profile.…”
Section: Glucosinolate Synthesis and Degradationmentioning
confidence: 75%
“…However, two myrosinase-like genes (BGL1, At1g52400 and At5g28510) were strongly up-regulated during K 1 starvation (average fold change of 8.6 and 7.6, respectively) and down-regulated upon K 1 resupply. Furthermore, several myrosinase-binding protein, homologs of which are induced by wounding and exogenous JA treatment in Brassica napus (Taipalensuu et al, 1997), showed the same expression profile.…”
Section: Glucosinolate Synthesis and Degradationmentioning
confidence: 75%
“…However, the antagonising effect of SA on the wound-mediated and ABA-mediated increase in the amount of MBP transcript is in accordance with the effect of SA on pin2 expression (Pena-Cortes et al, 1993). Moreover, as for the wound-inducible protease-inhibitor proteins in tomato (Doares et al, 1995) and the wound-inducible MAP in B. nupus (Taipalensuu et al, 1997a), an SA-sensitive step after JA has been identified in the signal-transduction pathway regulating the wound-inducible MBP. However, the antagonising effect of SA on JA induction of MBP was much more pronounced as compared with the effect on the JA-mediated MAP induction, which might indicate the presence of at least partially different signaltransduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The subcellular location of MAP has not been determined. However, the seed-MAP and the inducible-MAP transcripts seem to encode putative cleavable signal peptides (Taipalensuu et al, , 1997a, and MAP is a glycosylated protein that has been purified from a protein-body-enriched fraction (Falk et al, 1995a;Taipalensuu et al 1996), indicating that MAP might be targetted to the same compartment as myrosinases and MBP. Although it has not been demonstrated conclusively whether or not MAP transcripts are expressed in myrosin cells, from in situ hybridisations it is clear that the amount of MAP transcripts increases in most cells following MeJA treatment (Taipalensuu et al, 1997a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymes that catalyze the core reactions of glucosinolate biosynthesis have been identified (Wittstock and Halkier, 2002); however, a number of glucosinolates are further modified by additions of other substituents that include sinapoyl and benzoyl groups (Linscheid et al, 1980;Reichelt et al, 2002;Brown et al, 2003). This acylation may have an impact on glucosinolate turnover and plant-herbivore interactions because they are not readily degradable targets for myrosinases (Taipalensuu et al, 1997). The presence of benzoylated glucosinolates in Arabidopsis has already been demonstrated, and sinapoylated glucosinolates have been detected in Arabidopsis seed extracts (Graser et al, 2001;Reichelt et al, 2002).…”
Section: Candidate Reactions For Scpl Acyltransferases Can Be Found Tmentioning
confidence: 99%